Long‐Term Wage Fluctuations with Industry‐Specific Human Capital - Weinberg, Bruce A. (Journal of Labor Economics, 2001)
Exploiting long term interindustry demand shifts, this article provides evidence that (1) industry‐level wages do not respond to industry demand conditions; (2) at the industry level, the employment of young workers responds more to demand shifts than does the employment of experienced workers; and (3) the postdisplacement wages of displaced workers are strongly affected by demand in their predisplacement industries. These findings are consistent with a model in which worker's investments in industry‐specific skills pose a barrier to interindustry labor mobility and wages do not respond to spot labor market conditions.